ORY-1001 Suppresses Cell Growth and Induces Apoptosis in Lung Cancer Through Triggering HK2 Mediated Warburg Effect - Lu, Zhaoliang; Guo, Yanke; Zhang, Xiaoya; Li, Jing; Li, Leilei; Zhang, Shuai; Shan, Changliang (Frontiers in Pharmacology, 2018)
ORY-1001, an inhibitor of covalent lysine (K)-specific demethylase 1A (KDM1A), have been used as a therapy for the treatment of acute leukemia. However, the underlying mechanisms of anticancer are still not fully elucidated. Here, we report that KDM1A is highly expressed in lung cancers, where it apply to drive aggressive growth. Furthermore, lung cancer patients with higher KDM1A levels have worse survival outcomes than patients with lower KDM1A levels. Interestingly, ORY-1001significantly inhibited the cell proliferation, colony formation, cell cycle and induced apoptosis by regulating Warburg effect through controlling Hexokinases 2 (HK2) expression. In summary, these results indicates that ORY-1001 could inhibit the growth of lung cancer cells via regulating Warburg effect by controlling HK2.